Simplest Monodentate Imidazole Stabilization of the oxy‐Tyrosinase Cu2O2 Core: Phenolate Hydroxylation through a CuIII Intermediate. (21st July 2016) - Chiang, Linus; Keown, William; Citek, Cooper; Wasinger, Erik C.; Stack, T. Daniel P.
Abstract: Tyrosinases are ubiquitous binuclear copper enzymes that oxygenate to Cu II 2 O2 cores bonded by three histidine Nτ‐imidazoles per Cu center. Synthetic monodentate imidazole‐bonded Cu II 2 O2 species self‐assemble in a near quantitative manner at −125 °C, but Nπ‐ligation has been required. Herein, we disclose the syntheses and reactivity of three Nτ‐imidazole bonded Cu II 2 O2 species at solution temperatures of −145 °C, which was achieved using a eutectic mixture of THF and 2‐MeTHF. The addition of anionic phenolates affords a Cu III 2 O2 species, where the bonded phenolates hydroxylate to catecholates in high yields. Similar Cu III 2 O2 intermediates are not observed using Nπ‐bonded Cu II 2 O2 species, hinting that Nτ‐imidazole ligation, conserved in all characterized Ty, has functional advantage beyond active‐site flexibility. Substrate accessibility to the oxygenated Cu2 O2 core and stabilization of a high oxidation state of the copper centers are suggested from these minimalistic models.